PERFORMANCE ANALYSIS OF THE CUSTOMARY FOREST MANAGEMENT INSTITUTION OF MARGA SERAMPAS IN RANTAU KERMAS VILLAGE, JANGKAT DISTRICT, MERANGIN REGENCY - Abdul Khoiril Anam; Marwoto Marwoto; Rahmad Nurmansah (Universitas Muhammadiyah Palembang, 2026)
Customary forest is one of the social forestry schemes that grants indigenous communities legal rights to manage forest areas sustainably. The success of customary forest management is strongly influenced by the institutional performance of its management body. This study aimed to analyze the institutional performance of the Customary Forest Management Institution (LPHA) of Marga Serampas in Rantau Kermas Village, Jangkat District, Merangin Regency. The research was conducted in 2025 using a mixed methods approach integrating quantitative and qualitative methods. Data were collected through surveys, in-depth interviews, observation, and documentation studies involving 23 respondents selected through purposive sampling. Data were analyzed using descriptive quantitative methods with a Likert scale based on Ostrom’s (1990) eight institutional principles, and were further strengthened by descriptive qualitative analysis. The results showed that the institutional performance of LPHA Marga Serampas obtained a score of 67,72% and was categorized as good. Indicators of clearly defined boundaries, monitoring, recognition of rights to organize, and congruence between rules and local conditions showed good performance, while collective-choice arrangements and institutional strengthening still require improvement. These findings indicate that LPHA Marga Serampas has played a fairly effective role in supporting customary forest management; however, strengthening institutional capacity and community participation remains necessary to improve the effectiveness of sustainable customary forest management.